Education in the Syrian Golan Heights under international human rights law and international humanitarian law - Strucke, Michelle (AUC Knowledge Fountain, 2012)
Compulsory education, in particular history and religious education, is often used by states as a critical tool of nation building, as states attempt to socialize and shape the attitudes and beliefs of citizens in line with their strategic aims. As a state that defines itself as "Jewish and democratic" and that has instituted special compulsory education curricula for students on the basis of ethnicity and religion, the state of Israel is no exception. The Syrian Golan despite being under occupation by Israel for the last forty-five years has been written about only sparingly compared to the overwhelming amount of research that has been performed on the Occupied Palestinian Territories. The Druze residents of the Occupied Syrian Golan are subject to a separate compulsory education curriculum designed and implemented by the state of Israel that attempts to shape their identity in religious terms that reflect Israel's strategic aims at the expense of accurately depicting the history and heritage of the Syrian Golan and its residents. It attempts to obscure their identity as Syrian Arabs entirely, focusing instead on a narrative of historical similarity and alliance of Druze and Jews and their common persecution by Muslims. And most importantly, it is the same curriculum that Israel has created for its own citizens, highlighting a fundamental problem in Israel's denial that it occupies the Syrian Golan. The problem in the Syrian Golan is not simply that the residents receive a separate education on the basis of religious and ethnic difference. It is not simply that the residents are left without the option of choosing an alternative education for their children that respects their origins. It is that the abuse of the principle of non-annexation has fundamental consequences for the human dignity of the affected residents, and negative implications on the international legal system upon which the principle is based. This study undertakes to analyze the problem of education in the occupied Golan in relation to norms of IHRL and IHL and to propose reconciliation between these conflicting norms to the extent that it is possible. It will focus primarily on Israel's obligations under the ICESCR, CRC, CADE, and key international humanitarian agreements including the Fourth Geneva Convention and the Hague Regulations in the context of belligerent occupation. And finally, it will briefly analyze the problematic legal consequences of Israel's conduct in relation to the residents of the Syrian Golan, and the international legal system.